Stereoscopic particle image velocimetry measurements and proper orthogonal decomposition analysis of the in-cylinder flow of gasoline direct injection engine - El-Adawy, M. (2019)
Intake generated flows are known to have a fundamental influence on the combustion both in spark ignition (SI) and compression ignition engines. This study experimentally investigated the tumble flow structures inside a cylinder of gasoline direct injection (GDI) engine utilizing a stereoscopic time-resolved particle image velocimetry (PIV). The experiments were conducted in a GDI engine head for a number of fixed valve lifts and 150 mmH2O pressure difference across the intake valves. A tumble flow analysis was carried out considering different vertical tumble planes. In addition, the proper orthogonal decomposition (POD) identification technique was applied on the PIV data in order to spatially analyze the structures embedded in the instantaneous velocity data sets. The results showed that the flow was dominated by a strong tumble motion in the middle of cylinder at high valve lifts (8-10 mm). Moreover, it is worth pointing out that, because of the complexity of the flow at the high valve lifts, the flow energy was distributed over a higher number of POD modes. This was confirmed by the need of a higher number of POD modes needed to reconstruct the original velocity field to the same level of fidelity. Copyright Â© 2019 by ASME.